Synthesis, characterization and antimicrobial activity of Mn(ii) and Zn(ii) complexes with leucine and alanine - Jibrin Okpanaki, Hamza; A. D Onu, Dr; S.O. Idris, Prof. (International Journal of Advanced Chemistry, 2019)
Background: Transition metals are essential metallic element and they exhibit great biological activity. In recent time, researches have shown significant progress in the utilization of transition metal complexes as drugs for treatment of several human disorders like cancer, infections and neurological disorders, amongst others.Objective: The study attempted to obtain neutral complexes of MLn.nH2O type (M = Mn/Zn and L = leucine/alanine), characterize, and then study their biological activities.Methods: 2mmols of the ligands were dissolved each, in 20 ml distilled water and 0.33 ml of 30% NaOH was added. Then 1 mmol of the metal salts was dissolved in 2 ml of water and stirred, the salt solution was added to the solution of the ligand and stirred. The dark brown and white precipitates for manganese amino acid complex and zinc amino acid complexe respectively were filtered off, washed, dried in air and then weighed to establish the percent of complexation. The complexes were then subjected to both spectroscopic and non-spectroscopic method of analysis.Result: The result suggested the coordination of the ligand to the central metal.Conclusion: The results suggested monoclinic crystal system for all the complexes formed. The antimicrobial studies showed an enhanced biological sensitivity for the complexes when compared with that of the ligands, and the structure of the newly synthesized complexes were proposed to be octahedral for Mn-amino acid and tetrahedral for the Zn-amino acid.Â Â Â
Keywords: Antimicrobial Activities; Characterization; Molar Conductivity; Synthesis; X-Ray Diffraction.